Sebatian aroma dalam minyak Citrus grandis (Aroma compounds in Citrus grandis oil) - Omar, Muhammad Nor (Malaysian Agricultural Research and Development Institute, 1999)
The essential oil of Citrus grandis was prepared from fresh peel by steam distillation and Likens-Nickerson extraction methods. The oils were then analysed by means of capillary gas chromatography (GC), gas chrmatography and mass spectrometer GC-MS, Kovats retention indices, odour evaluation and column fractionation on silica gel. Fourty three aroma constituents were identified in the oil. Among them are 8 monoterpenes, 4 sesquiterpene hydrocarbons, 6 esters, 5 carbonyls and 13 alcohols, which contributed to the aroma of C. grandis. Nootkatone was also identified in the oxygenated portion after fractionation on silica gel column. The presence of elemicin (l,2,6-trimethoxy-4-allylbenzene) and perillene (p-isohexenyl-furan) has made this oil different from the other citrus peel oils